Foretelling the Future: Predicting STI Diagnosis and Its Implications for Ending the HIV Epidemic among Black Men Who Have Sex with Men - Burns, Paul A. (J Urban Health, 2020)
Despite evidence of the link between STI and HIV transmission, STI rates remain alarmingly high, particularly among racial/ethnic minorities. This study examined the relationship between earlier STI diagnoses (gonorrhea and chlamydia) and future STI acquisition and its implications for HIV prevention among a sample of urban Black men who have sex with men (Black MSM). Data from a cohort of 600 Black MSM (15–29 years of age) residing in a medium-size Southern city enrolled in a HIV prevention intervention were analyzed. We used multivariate logistic regression to assess the association between STI diagnosis (baseline: Time 1) and subsequent STI diagnosis (90-day post-diagnosis: Time 2). Repeated measures analyzed at Time 1 and Time 2 included condomless sex, insertive and receptive sex, concurrent sexual partnerships, multiple partners, and age of partner. Independent of socio-demographic factors, we found having a prior GC/CT increased the likelihood of a future GC/CT by a factor of 15 (OR = 15.2, p = 0.01). Participants were statistically more likely to have been diagnosed with an extragenital STI (OR = 2.3, p = 0.05). Present findings suggest that time of initial STI diagnosis is a critical period in which to intervene to reduce future STI/HIV acquisition. Screening guidelines should be expanded to include testing for extragenital infection. STI screening and treatment and counseling programs should be culturally appropriate to account for the unique needs and the social and environmental context of the population. Additional research is needed to design STI prevention interventions that address social and environmental factors to reduce sexual risk behaviors that increase HIV vulnerability for Black MSM.